2020
DOI: 10.1039/d0nh00145g
|View full text |Cite
|
Sign up to set email alerts
|

Piezochromic luminescence in all-inorganic core–shell InP/ZnS nanocrystals via pressure-modulated strain engineering

Abstract: The piezochromic luminescence and lattice mismatch with pressure in all-inorganic core–shell InP/ZnS nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…Figure 2d shows that the slope of the pressure‐dependent emission energy function changes significantly around 5.3 GPa. The experimental data are well fitted to the linear equation [ 20 ] EP= E0+αP where E 0 = 2.35 eV is the emission energy at ambient pressure and can be obtained by experiments; α is the pressure coefficient derived from the fit of the experimental data. The absolute value of the coefficient α = −65 meV GPa −1 at low‐pressure regime is bigger than the one at high‐pressure regime (α = −32 meV GPa −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2d shows that the slope of the pressure‐dependent emission energy function changes significantly around 5.3 GPa. The experimental data are well fitted to the linear equation [ 20 ] EP= E0+αP where E 0 = 2.35 eV is the emission energy at ambient pressure and can be obtained by experiments; α is the pressure coefficient derived from the fit of the experimental data. The absolute value of the coefficient α = −65 meV GPa −1 at low‐pressure regime is bigger than the one at high‐pressure regime (α = −32 meV GPa −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…29 Until now, it has been reported that InP as a core prevents the formation of a coherent core/shell structure. 30 This is due to a higher bulk modulus for InP ( B u = 72.3 GPa) than the strain-tolerated materials such as CdTe ( B u = 42.4 GPa) and CdSe ( B u = 53.1 GPa), 28,31 suggesting that InP is less deformable even under isotropic compressive strain by shell encapsulation. However, we obtained the results of a series of structural and optical characterization studies which defy this common understanding.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the largest piezochromic PL tuning range in the visible light range for traditional inorganic semiconductor nanomaterials. 26,35,36 Simultaneously, an ultrabroad bandgap tunability range was observed from 1.99 eV (0 GPa) to 2.45 eV (approximately 14.2 GPa). In addition, in situ small-angle synchrotron X-ray scattering (SAXS) measurements and transmission electron microscopy (TEM) images demonstrated that core–shell InP/ZnSe NCs were sintered under high pressure, resulting in the formation of two-dimensional (2D) nanostructures.…”
Section: Introductionmentioning
confidence: 86%